(untitled) (Revista Nacional de Odontología, 2021)
Introduction: the objective of this work is to review the topic and report the case of a 9-year-old female patient with a supernumerary fused to the upper left side. Methods: the double tooth is an alteration during odontogenesis that refers to teeth joined by fusion or gemina-tion. Their differentiation represents a challenge in diagnosis and subsequent treatment; hence the importance of reviewing the topic and presenting this clinical case. A fusion in the anterior segment, in addition to affecting the masticatory function, altering the dental arch space and compromising the periodontium, represents aes-thetic problems of difficult solution that require a comprehensive analysis. Results: in the clinical examination, a double tooth was observed that caused crowding and lack of space for the canine eruption. The radiographic examination revealed two teeth fused by the crown and the middle third of the root. His treatment consisted of waiting for the complete closure of the roots to proceed to hemisection, extraction of the supernumerary and placement of removable orthodontic appliances, as well as follow-up for forty months, observing a periodontally healthy tooth with partial obliteration of the lumen of the root canal without change. color. Conclusions: in the fusion of an anterior tooth and a supernumerary one, the radiological examination is neces-sary for the adequate differential diagnosis with other number anomalies such as gemination. Hemisection and removable appliances can be considered as an aesthetic and functionally appropriate treatment alternative, as well as its subsequent clinical and radiographic follow-up.